2012
DOI: 10.1159/000339839
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Differentiation of Adult Adipose Mesenchymal Stem Cells into Retinal Progenitor Cells

Abstract: Introduction: It has been previously shown that adult mesenchymal stem cells (MSCs) differentiate into neural progenitor cells (NPCs) and that the differentiation process was completed in 24–48 h. In this previous study, MSCs from a bone marrow or fat source were co-incubated with homologous autoaggressive cells (ECs) against nerve tissue, and these NPCs were successfully used in human regenerative therapeutic approaches. The present study was conducted to investigate whether a similar differentiation method c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Several studies have shown that these cells are capable of differentiating into numerous cell types, and differentiation is not restricted to their initial tissue type [9,38,39]. One of the major downsides of ASCs represents their high variability and loss of differentiation capacity at higher passage numbers after expansion in vitro [15,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that these cells are capable of differentiating into numerous cell types, and differentiation is not restricted to their initial tissue type [9,38,39]. One of the major downsides of ASCs represents their high variability and loss of differentiation capacity at higher passage numbers after expansion in vitro [15,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for RPE replacement foresees the use of mesenchymal stem cells, opportunely differentiated into RPE cells (Duan et al 2013;Moviglia et al 2012). The amniotic fluid may represent an interesting source, since it contains AF-MSCs characterized by a high proliferative and differentiative potential, also towards neurogenic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, the findings of Moviglia et al [1] fall short of providing evidence for their conclusions, for the following reasons:…”
Section: Identity Of Mesenchymal Stem Cells: ‘Stemness'mentioning
confidence: 95%
“…We read the paper by Moviglia et al [1] entitled ‘In vitro differentiation of adult adipose mesenchymal stem cells into retinal progenitor cells', published in Opthalmic Research, with great interest.…”
Section: Identity Of Mesenchymal Stem Cells: ‘Stemness'mentioning
confidence: 99%
See 1 more Smart Citation